BAT CAVE: A RIVER TOURISM DESTINATION IN BUKIT LAWANG PRESERVED TO PREVENT LOCAL COMMUNITY CONFLICTS - Syaifuddin, Prof. Wan; Loebis, Dra. Roma Ayuni A. (Prosiding Konferensi Internasional Kesusasteraan, 2025)
Landak River is a tourist destination in the Landak River stream. Its main attraction is the story found in the text Bat Cave or Goa Kelelawar. Along with the story of Goa Kelelawar (Bat Cave) conveys ideas and thoughts for a religious and harmonious life that is truly enchanting. The reality of the Bat Cave story has transformed from an oral tradition to a discourse of reality to an object of the will of its audience to avoid conflict among fellow citizens in Bukit Lawang Bahorok Langkat. The existence of the text content and context of the Bat Cave story in its audience’s region is bound by two principles, namely de facto and de jure. The purpose of the discussion shows that the community of the Bat Cave story lies in the form and meaning of the symbols in the story, not merely in the language. The meaning of the story differs from the meaning of everyday language and functions as a means of expression for the community and influences behavior in order to convey something that strengthens the bonds between residents by explaining both abstract and concrete rules. The discussion shows that it is interesting or fascinating because it avoids the conflicts of the community. The research refers to the methods and approaches of literary anthropology with conflict theory, which is a state of opposition or struggle due to differences in objectives between two or more parties on an issue. The discussion shows that resolving conflicts in the Bukit Lawang Bahorok Langkat community outlines five levels of ending conflicts. All levels are conveyed in the Goa Kelelawar story to the community in the story region through the embodiment of its discourse.